Application of Bonded Joints for Quantitative Analysis of Adhesion. (16th March 2016) - Trpčevská, Jarmila; Kollárová, Mária; Zdravecká, Eva; Tkáčová, Jana
Abstract : The performance of hot-dip coated steel sheets is associated with properties of the zinc coatings on steel substrate. For the characterization of the adhesion behaviour of zinc coating on steel various tests were employed. The study was focused on quantification assessment of galvanized coating adhesion to substrates. Methods for evaluation of the bonding strength of zinc coating by the shear strength and the T-peel tests applying four special types of adhesives were used. The experimental tests of bonded joints show that the adhesion of the zinc coating to the substrate was higher than that of the applied adhesive with the highest strength.